2021
DOI: 10.1017/age.2021.2
|View full text |Cite
|
Sign up to set email alerts
|

Farm Producers' Household Consumption and Individual Risk Behavior after Natural Disasters

Abstract: Understanding how farm household consumption responds to adverse income shocks can provide insight into household well-being and appropriate agricultural policy. Using a split-sample survey of Indiana specialty producers, where we randomly assign respondents to treatments that vary the size of a hypothetical income shock, we estimate the relationship between income loss and household consumption. Given that postdisaster producers' risk preferences are important for business decisions, we elicit producers' risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…The Agricultural and Resource Economics Review, with H-index of 27, concentrates again on carrying out empirical studies on the agricultural sector, not looking at crops and consumers' reactions, although such studies are mainly related to US, where economic losses are estimated for given areas of the country (as in Wahdat et al, 2021).…”
Section: Agriculturementioning
confidence: 99%
“…The Agricultural and Resource Economics Review, with H-index of 27, concentrates again on carrying out empirical studies on the agricultural sector, not looking at crops and consumers' reactions, although such studies are mainly related to US, where economic losses are estimated for given areas of the country (as in Wahdat et al, 2021).…”
Section: Agriculturementioning
confidence: 99%
“…Existing research found that natural disasters affect individuals' well-being (Rehdanz et al, 2015), investor sentiment (Hirshleifer and Shumway, 2003;Kamstra et al, 2003;Kaplanski and Levy, 2010), migration (Saldaña-Zorrilla and Sandberg, 2009;Warner and Afifi, 2014;Cattaneo and Peri, 2016;Pajaron and Vasquez, 2020), risk preferences (Bourdeau-Brien and Kryzanowski, 2020), mental health (Shultz, 2014;Graham et al, 2019;Zhang et al, 2022), and children's development (Rabassa et al, 2012;Deuchert and Felfe, 2015). Furthermore, studies have examined the impact of natural disasters on household income inequality (Yamamura, 2015;Abdullah et al, 2016;Keerthiratne and Tol, 2017), household savings (Filipski et al, 2019), household debt (Gallagher and Hartley, 2017), household consumption (Arndt et al, 2004;Wahdat, et al, 2021), and other household behaviors. Natural disasters cause direct or indirect economic losses to households.…”
Section: Introductionmentioning
confidence: 99%